2021
DOI: 10.1152/physiolgenomics.00159.2020
|View full text |Cite
|
Sign up to set email alerts
|

Distinct uterine artery gene expression profiles during early gestation in the stroke-prone spontaneously hypertensive rat

Abstract: During pregnancy the uterine spiral arteries undergo major vascular remodelling to ensure sufficient uteroplacental perfusion to support the fetus. In pregnancies complicated by hypertensive disorders this remodelling is deficient leading to impaired uteroplacental blood flow and poor maternal and fetal outcomes. The underlying genetic mechanisms for failed vascular remodelling are not fully understood. This study aimed to examine the early-pregnancy associated gene changes in the uterine arteries of stroke-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…We are confident that our analysis is valid as we were able to demonstrate differential regulation of some of the key pathogenetic principles including RAAS activation and oxidative stress in these models. In line with our proteomic data, Scott et al, through transcriptomics of uterine arteries show an elevated immune response, and increased production of reactive oxygen species and downstream effectors of the RAAS in pregnant SHRSP (38).…”
Section: Shrsp Versus Transgenic Sd-pesupporting
confidence: 91%
“…We are confident that our analysis is valid as we were able to demonstrate differential regulation of some of the key pathogenetic principles including RAAS activation and oxidative stress in these models. In line with our proteomic data, Scott et al, through transcriptomics of uterine arteries show an elevated immune response, and increased production of reactive oxygen species and downstream effectors of the RAAS in pregnant SHRSP (38).…”
Section: Shrsp Versus Transgenic Sd-pesupporting
confidence: 91%
“…A recent study applying RNA sequencing of spontaneously hypertensive stroke-prone rats (SHRSP) found that the gene expression pattern of pregnant SHRSP uterine arteries was dominated by increased reactive oxygen species and downstream effectors of the renin-angiotensin-aldosterone system. The disrupted pathway involved may contribute to adverse vascular remodeling and the resultant placental ischemia and systemic vascular dysfunction ( 39 ). Uterine spiral artery remodeling is essential for promoting blood flow to the placenta and fetal development, and omics could help us better understand this process.…”
Section: Omics Studies Investigating the Establishment And Maintenanc...mentioning
confidence: 99%